2022
DOI: 10.47626/2237-6089-2021-0449
|View full text |Cite
|
Sign up to set email alerts
|

Levels of impulsivity in individuals with cannabis use disorder

Abstract: Introduction: Substance use disorder consists of the presence of cognitive, behavioral, and physiological symptoms, indicating continuous use of one or more substances by the individual. The literature points to the existence of a relationship between impulsive behavior, in which individuals tend to act thoughtlessly and with a lower level of planning, and consumption of substances including cannabis. Objectives: To examine the presence and severity of impulsivity in individuals with cannabis use disorder and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…In humans, marijuana use has been associated with increased impulsivity when given in an acute ( 52 ) or chronic manner ( 53 ). Concomitantly, individuals with CUD have been shown to present increased impulsivity ( 54 ). Interestingly, impulsivity is suggested to predispose compulsivity, which leads to drug abuse and addiction ( 55 , 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, marijuana use has been associated with increased impulsivity when given in an acute ( 52 ) or chronic manner ( 53 ). Concomitantly, individuals with CUD have been shown to present increased impulsivity ( 54 ). Interestingly, impulsivity is suggested to predispose compulsivity, which leads to drug abuse and addiction ( 55 , 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found substance use to be associated with MI. Wagner et al ( 64 ) for instance, found MI to be significantly associated with alcohol use among a sample of individuals with cannabis use disorder, with greater alcohol use being associated with greater difficulties in being able to inhibit their responses ( 64 ). Similarly, Fox et al ( 65 ) found MI (among other factors) to be independently predictive of alcohol use among a community sample of regular drinkers.…”
Section: Discussionmentioning
confidence: 99%
“…Thiago M. Fidalgo, 1,2,5 Lisia von Diemen 3,4,5 Marijuana is the illicit drug most used worldwide, with more than 200 million people using it worldwide in 2019, 1 representing around 4% of the global population. This alone would be a solid argument to justify the producing this special issue of Trends in Psychiatry and Psychotherapy.…”
Section: Current State Of the Global Impact Of Cannabis Usementioning
confidence: 99%
“…This exciting supplement features two original articles, one addressing the role of friends in young cannabis users 2 and the other, the clinical correlates of impulsivity in cannabis use disorder. 3 Along with this, we have two reviews covering critical aspects of the world's epidemiology, policies, legalization, and outcomes of the non-medical use of cannabis. 4,5 Two editorials from leading experts in the field round out this issue, exploring distinct facets of cannabis legalization and its outcomes.…”
Section: Current State Of the Global Impact Of Cannabis Usementioning
confidence: 99%